Epoxy resin composition, reinforcement fiber-containing epoxy resin composition, prepreg, thermoplastic resin, and fiber-reinforced plastic using the same
Patent Information
- Application Number
- JP2023138425
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-03-12
AI Technical Summary
【0022】 本発明のエポキシ樹脂組成物から得られる熱可塑性樹脂は、衝撃特性に優れ、また衝撃特性に優れた繊維強化プラスチック(FRTP)を提供することができる。
Smart Images

Figure 2025032910000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic resin, an epoxy resin composition, a reinforcing fiber-containing epoxy resin composition, a prepreg, and a fiber-reinforced plastic using these. [Background technology]
[0002] In recent years, there has been a demand for further improvements in impact resistance for components used in applications such as electronic devices, battery cases, motor protective tubes, mobile structures, sporting goods, and prosthetic limbs.
[0003] Fiber-reinforced plastics (FRP) exhibit excellent physical properties such as light weight and high strength, and among them, those using carbon fiber as the reinforcing fiber (CFRP) are known to have particularly excellent mechanical strength. Among CFRPs, those that use thermoplastic resin as the base resin are called CFRTPs, and are expected to have excellent secondary processability and recyclability.
[0004] The impact strength of ordinary thermosetting epoxy resin is 5kJ / m 2 It is known that the impact strength of CFRP with epoxy resin as the matrix is about 200 kJ / m 2 (Charpy notched impact test) has been shown to be of the same order of magnitude.
[0005] Polycarbonate is 80kJ / m 2 It is known that it shows excellent impact strength (notched Charpy impact test), but Non-Patent Document 2 states that the impact strength of CFRTP using polycarbonate as the base resin is 150 kJ / m 2 It has been shown to be to an extent.
[0006] In order to achieve sufficient impact strength as CFRP, it is necessary to improve the impact strength of the base resin and also ensure adhesion at the interface between the fibers and the resin.
[0007] Epoxy resins are mainly used as the base material (matrix) resin of FRP because of their excellent balance between price and physical properties. Among them, Patent Document 1 proposes a method in which an epoxy resin and a phenolic hydroxyl group-containing compound are mixed with reinforcing fibers in advance, and polymerized by polyaddition reaction using a polymerization catalyst and a reaction retarder to form a fiber-reinforced thermoplastic resin. Patent Document 2 proposes polyaddition reaction of a bifunctional epoxy resin with a bifunctional compound having a functional group selected from the group consisting of a phenolic hydroxyl group, an amino group, a carboxyl group, a mercapto group, an isocyanate group, and a cyanate ester group. Such epoxy resins are also called in-situ polymerized thermoplastic epoxy resins, and FRPs using such epoxy resins are expected to be excellent in mass production, moldability, and recyclability. In-situ polymerized thermoplastic epoxy resins are impregnated into fibers in a low viscosity state before polymerization, so they have good impregnation properties, can increase the proportion of reinforcing fibers, and are superior in impact strength and toughness compared to when general-purpose thermosetting epoxy resins are used.
[0008] For example, Patent Document 3 discloses a method for obtaining a phenoxy resin having a large degree of branching by reacting the phenoxy resin, which is a thermoplastic resin, in the presence of an organic phosphonium salt catalyst.
[0009] Here, Non-Patent Document 3 shows that the branching structure of a resin affects mechanical properties and that the branching structure can be evaluated by using light scattering GPC. Non-Patent Document 4 shows a method of simultaneously analyzing by connecting an RI detector and a viscosity detector in series to light scattering GPC (GPC-LALS).
[0010] It is known that the branched structure can be evaluated by the slope α of the Mark-Houwink-Sakurada plot (MH plot) when the plot is arranged. The closer the value of α is to 1, the less branched the structure is. Non-Patent Documents 5 and 6 show a method of using α as an index to evaluate the degree of branching. In particular, Fig. 4 of Non-Patent Document 6 is a graph in which the intrinsic viscosity (η) is plotted against the absolute molecular weight (M) in a double logarithmic plot (MH plot). [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2006-321897 A [Patent Document 2] International Publication No. 2004 / 060981 [Patent Document 3] JP 2017-171802 A [Non-patent literature]
[0012] [Non-Patent Document 1] Journal of the Society of Materials Science,Japan,Vol.43,No.487,pp.482-488,Apr.1994 [Non-Patent Document 2] Journal of the Society of Materials Science,Japan,Vol.60,No.3,pp.251-258,Mar.2011 [Non-Patent Document 3] Polymer, Vol. 30, July (1981), P540-545 [Non-Patent Document 4] Journal of the Society of Rubber Science and Technology of Japan, Vol. 60, No. 11 (1987), pp. 636-643 [Non-Patent Document 5] Thermosetting Resins, Vol. 6, No. 3 (1985), P127-134 [Non-Patent Document 6] Starch Science, Volume 36, No. 4 (1989), P257-264 Summary of the Invention [Problem to be solved by the invention]
[0013] An object of the present invention is to provide an in situ polymerization type epoxy resin composition and a prepreg which are suitable for use in in situ polymerization type fiber reinforced thermoplastic resins and which are capable of obtaining fiber reinforced thermoplastic resins having excellent impact properties. [Means for solving the problem]
[0014] As a result of intensive investigations aimed at solving the above-mentioned problems, the present inventors have discovered that a fiber-reinforced thermoplastic resin with excellent impact properties can be obtained by using a linear thermoplastic epoxy resin with a low degree of branching, in which the slope α of the Mark-Houwink-Sakurada plot (MH plot) in the absolute molecular weight (M) range of 50,000 to 100,000 is between 0.45 and 0.80, and have thus completed the invention.
[0015] That is, the present invention provides an epoxy resin composition which contains, as essential components, an epoxy resin (A) having two epoxy groups in one molecule, a compound (B) having two functional groups reactive with epoxy groups in one molecule, and a polymerization catalyst (D), and which becomes a thermoplastic resin through a polymerization reaction, The blending amounts of the epoxy resin (A) and the compound (B) are 0.90 to 1.10 mol of the compound (B) per 1 mol of the epoxy resin (A), The thermoplastic resin polymer obtained by polymerizing the epoxy resin composition is an epoxy resin composition characterized in that the slope α of the Mark-Houwink-Sakurada plot (MH plot) in the absolute molecular weight (M) range of 50,000 to 100,000 measured by light scattering GPC is 0.45 or more and 0.80 or less.
[0016] The blending amount of the polymerization catalyst (D) is preferably 0.01 parts by weight or more and 10 parts by weight or less based on 100 parts by weight of the total amount of the epoxy resin (A) and the compound (B).
[0017] It is preferable that the epoxy resin composition does not contain an organic solvent, or if it contains an organic solvent, the content of the organic solvent is 0.01% by weight or more and 10% by weight or less of the epoxy resin composition, and that the epoxy resin (A) and the compound (B) are uniformly dissolved.
[0018] The present invention also relates to a reinforcing fiber-containing epoxy resin composition, characterized by containing the above-mentioned epoxy resin composition and reinforcing fiber (F). The reinforcing fiber (F) is preferably a short fiber or continuous fiber having a length of 1 mm or more. The reinforcing fiber (F) is preferably a carbon fiber, and is preferably contained in an amount of 20% by weight to 80% by weight.
[0019] The present invention also relates to a prepreg made of the above-mentioned reinforcing fiber-containing epoxy resin composition, a fiber-reinforced plastic using the above-mentioned reinforcing fiber-containing epoxy resin composition, and a fiber-reinforced plastic using the above-mentioned prepreg.
[0020] The present invention also relates to a thermoplastic resin obtained from the above-mentioned epoxy resin composition, characterized in that the slope α of a Mark-Houwink-Sakurada plot (MH plot) measured by light scattering GPC at an absolute molecular weight (M) of 50,000 to 100,000 is 0.45 or more and 0.80 or less.
[0021] The present invention also relates to a prepreg made of the above thermoplastic resin and reinforcing fibers (F), a fiber-reinforced plastic made of the above thermoplastic resin and reinforcing fibers (F), and a fiber-reinforced plastic using the above prepreg. Effect of the Invention
[0022] The thermoplastic resin obtained from the epoxy resin composition of the present invention has excellent impact properties, and can provide fiber reinforced plastics (FRTP) having excellent impact properties. [Brief description of the drawings]
[0023] [Figure 1] 1 shows an MH plot of the polymer obtained in Example 1, where the vertical axis is the logarithm of intrinsic viscosity (η) and the horizontal axis is the logarithm of absolute molecular weight (M). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The present invention will be described in detail below based on preferred embodiments thereof. The epoxy resin composition (E) of the present invention is an epoxy resin composition that contains, as essential components, an epoxy resin (A) having two epoxy groups in one molecule, a compound (B) having two functional groups reactive with epoxy groups in one molecule, and a polymerization catalyst (D), and becomes a thermoplastic resin through a polymerization reaction. This composition may contain additives such as reinforcing fibers (F), organic solvents, fillers, and flame retardants. In this specification, the epoxy resin (A) having two epoxy groups in one molecule may be referred to as "epoxy resin (A)" or "bifunctional epoxy resin (A)". The compound (B) having two functional groups reactive with the epoxy groups in one molecule may be referred to as "compound (B)" or "bifunctional compound (B)". In addition, when simply referring to a "resin composition", it refers to both an "epoxy resin composition" and a "reinforcing fiber-containing epoxy resin composition".
[0025] The thermoplastic resin obtained by polymerizing the epoxy resin composition has a slope α of 0.45 or more and 0.80 or less at an absolute molecular weight (M) of 50,000 to 100,000 in a Mark-Houwink-Sakurada plot (MH plot) measured by light scattering GPC.
[0026] The thermoplastic resin obtained by polymerizing the epoxy resin composition is a high molecular weight phenoxy resin. The branched structure of the phenoxy resin was evaluated by the slope α of the MH plot at absolute molecular weights (M) of 50,000 to 100,000. The closer the value of α is to 0, the more the structure resembles a sphere with many branches, and the closer the value is to 1, the more linear the structure with few branches.
[0027] For the evaluation of branching, the slope α of the MH plot was used in the absolute molecular weight (M) range of 50,000 to 100,000. In the region where the absolute molecular weight (M) is less than 50,000, the difference in slope due to the branching degree is small, making it unsuitable for use in evaluating the branching degree. In the region of molecular weights of 100,000 or more, the volume occupied by the molecular weight distribution is small, making it unsuitable for use as an evaluation value.
[0028] The slope α of the MH plot is 0.45 or more, more preferably 0.47 or more, and even more preferably 0.50 or more. If the slope α is below the lower limit of the range, the branched structure will be too many, and the impact strength will not be fully exhibited. There is no upper limit for the slope α, but in the case of phenoxy resin, it is usually 0.80 or less.
[0029] The slope α of the MH plot was measured using the following measurement equipment and measurement conditions. The molecular abundance ratio (area per minute section / area of the entire peak) was calculated using an RI detector. The absolute molecular weight (M) for each minute section was analyzed using a light scattering detector, and the intrinsic viscosity (η) was analyzed using a viscosity detector. An MH plot was created from the absolute molecular weight (M) and intrinsic viscosity (η) values, and the slope α was calculated for absolute molecular weights (M) in the range of 50,000 to 100,000. Measurement device: OMNISEC (Malvern) Column: TSKgel guardcolumn MP(XL) + TSKgel Multipore HXL-M + TSKgel G1000HXL (all manufactured by Tosoh Corporation) connected in series Detector: Differential refractive index detector (RI detector) + light scattering detector (RALS 90°, LALS 7°) + viscosity detector Data processing: OMNISEC-11.10 (Malvern) Measurement conditions: Column temperature 40℃ Developing solvent: Tetrahydrofuran (THF) Flow rate 1.0mL / min Sample: 0.02 g dissolved in 10 mL of THF, filtered through a 0.20 μm microfilter (100 μL).
[0030] The weight average molecular weight (Mw) of the thermoplastic resin (phenoxy resin) obtained by polymerizing the epoxy resin composition (E) is preferably 40,000 or more and 200,000 or less. If the Mw of the thermoplastic resin is below the lower limit of the range, it will contain a large amount of compounds that have not been sufficiently polymerized, and there is a risk of the mechanical strength being deteriorated. On the other hand, if the Mw of the thermoplastic resin is above the upper limit of the range, the crosslinking reaction will have progressed, and there is a risk of the thermoplasticity being impaired. Mw is preferably 45,000 or more and 150,000 or less, more preferably 50,000 or more and 120,000 or less.
[0031] The epoxy equivalent of the thermoplastic resin is preferably 10,000 g / eq or more. If the epoxy equivalent is less than 10,000 g / eq, polymerization may not proceed sufficiently. The epoxy equivalent is more preferably 20,000 g / eq or more, and even more preferably 25,000 g / eq or more. The glass transition temperature (Tg) of the thermoplastic resin is preferably 90° C. or higher, more preferably 100° C. or higher, and even more preferably 120° C. or higher.
[0032] The epoxy resin (A) used in the epoxy resin composition (E) may suitably have an epoxy equivalent in the range of 100 g / eq. to 500 g / eq. The lower limit is preferably 150 g / eq., more preferably 180 g / eq. The upper limit is preferably 300 g / eq., more preferably 280 g / eq.
[0033] The purity of the epoxy resin (A) is preferably 95% by weight or more. If the epoxy resin (A) contains monofunctional impurities, the molecular weight after polymerization may not increase, and the mechanical properties of the obtained thermoplastic resin product may deteriorate. Therefore, the monofunctional impurities are preferably 2% by weight or less relative to the epoxy resin (A). If the epoxy resin (A) contains trifunctional or higher impurities, the impurities tend to form crosslinked structures starting from the impurities, which may increase the dispersion of the polymerized product and may gel and impair the thermoplastic properties. Therefore, the trifunctional or higher impurities are preferably 1% by weight or less relative to the epoxy resin (A). If the epoxy resin (A) has a high purity, it may contain positional isomers or oligomers. The epoxy resin (A) may be used alone or in combination of multiple types.
[0034] Examples of the epoxy resin (A) include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol E type epoxy resin, bisphenol Z type epoxy resin, bisphenol S type epoxy resin, bisphenol AD type epoxy resin, bisphenol acetophenone type epoxy resin, bisphenol trimethylcyclohexane type epoxy resin, bisphenol fluorene type epoxy resin (e.g., ZX-1201 (manufactured by Nippon Steel Chemical & Material Co., Ltd.)), biscresol fluorene type epoxy resin (e.g., OGSOL Bisphenol type epoxy resins such as tetramethylbisphenol A type epoxy resin, tetramethylbisphenol F type epoxy resin (e.g., YSLV-80XY (Nippon Steel Chemical & Material Co., Ltd.)), tetra-t-butylbisphenol A type epoxy resin, tetramethylbisphenol S type epoxy resin, dihydroxydiphenyl ether type epoxy resin, thiodiphenol type epoxy resin, and tetrabromobisphenol A type epoxy resin; biphenol type epoxy resin, tetramethylbiphenol type epoxy resin (e.g., YX4000 (Mitsubishi Chemical Co., Ltd.)); Examples of epoxy resins that can be used include epoxy resins manufactured by Epoxy Polymer Co., Ltd.), biphenol type epoxy resins such as dimethylbiphenol type epoxy resins and tetra-t-butylbiphenol type epoxy resins, benzenediol type epoxy resins such as hydroquinone type epoxy resins, methylhydroquinone type epoxy resins, dibutylhydroquinone type epoxy resins, resorcin type epoxy resins and methylresorcin type epoxy resins, dihydroxyanthracene type epoxy resins, hydroanthrahydroquinone type epoxy resins, dihydroxynaphthalene type epoxy resins, bisnaphtholfluorene type epoxy resins, and diphenyldicyclopentadiene type epoxy resins.
[0035] In particular, it is preferable to contain an epoxy resin (a) represented by the following general formula (1). In this case, the epoxy resin (A) contains the epoxy resin (a) at a content of preferably 50% by weight or more, more preferably 66% by weight or more, even more preferably 75% by weight or more, and particularly preferably 80% by weight or more. The epoxy resin (a) constitutes a part of the epoxy resin (A). [ka]
[0036] In formula (1), A is a divalent group represented by the following formula (2): n is the number of repetitions and its average value is 0 to 5, and preferably 0.1 to 1. [ka]
[0037] In formula (2), X is any one of a single bond, a hydrocarbon group having 1 to 13 carbon atoms, -O-, -CO-, -COO-, -S-, and -SO2-. The hydrocarbon group having 1 to 13 carbon atoms is preferably an alkylene group having 1 to 9 carbon atoms or an arylene group having 6 to 13 carbon atoms, and examples thereof include -CH2-, -CH(CH3)-, -C(CH3)2-, -C(CF3)2-, -CHPh-, -C(CH3)Ph-, 1,1-cyclopropylene group, 1,1-cyclobutylene group, 1,1-cyclopentylene group, 1,1-cyclohexylene group, 4-methyl-1,1-cyclohexylene group, 3,3,5-trimethyl-1,1-cyclohexylene group, 1,1-cyclooctylene group, 1,1-cyclononylene group, 1,2-ethylene Examples of such groups include 1,2-cyclopropylene, 1,2-cyclobutylene, 1,2-cyclopentylene, 1,2-cyclohexylene, 1,2-phenylene, 1,3-propylene, 1,3-cyclobutylene, 1,3-cyclopentylene, 1,3-cyclohexylene, 1,3-phenylene, 1,4-butylene, 1,4-cyclohexylene, 1,4-phenylene, 1,1-fluorene, 1,2-xylylene, 1,4-xylylene, tetrahydrodicyclopentadienylene, and tetrahydrotricyclopentadienylene. Ph represents a phenyl group. Among these, X is preferably a single bond, -O-, -CO-, -COO-, -S-, -SO2-, -CH2-, -CH(CH3)-, -C(CH3)2-, -CHPh-, -C(CH3)Ph-, 1,1-cyclohexylene group, 4-methyl-1,1-cyclohexylene group, 3,3,5-trimethyl-1,1-cyclohexylene group, 1,4-cyclohexylene group, 1,4-phenylene group, or 1,1-fluorene group, and more preferably a single bond, -O-, -CO-, -COO-, -S-, -SO2-, -CH2-, -CH(CH3)-, -C(CH3)2-, -C(CH3)Ph-, 1,1-cyclohexylene group, 3,3,5-trimethyl-1,1-cyclohexylene group, or 1,1-fluorene group. In addition, Ph represents a phenyl group. The alkylene group is meant to include an alkylidene group.
[0038] Y 1 are independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an aryl group having 6 to 10 carbon atoms. Examples of the alkyl group having 1 to 4 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an iso-propyl group, an n-butyl group, a sec-butyl group, an iso-butyl group, and a t-butyl group. Examples of the aryl group having 6 to 10 carbon atoms include a phenyl group, a tolyl group, an ethylphenyl group, a xylyl group, an n-propylphenyl group, an isopropylphenyl group, a mesityl group, and a naphthyl group. Of these, a methyl group, an ethyl group, an n-propyl group, an n-butyl group, a t-butyl group, a phenyl group, a tolyl group, a xylyl group, or a naphthyl group is preferred, and a methyl group, an ethyl group, an n-propyl group, an n-butyl group, a t-butyl group, a phenyl group, or a tolyl group is more preferred.
[0039] Y 2 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an aryl group having 6 to 10 carbon atoms, and a group other than a hydrogen atom is preferable. Examples of the alkyl group and aryl group include the above-mentioned Y 1 The preferred Y 2 is Y 1 is the same as: Y3 are independently any one of a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, and an aryl group having 6 to 10 carbon atoms. Examples of the alkyl group and the aryl group include Y 1 The preferred Y 3 is a hydrogen atom or Y 1 is the same as:
[0040] Examples of the epoxy resin (a) include tetramethylbisphenol F type epoxy resin, tetramethylbiphenol type epoxy resin, biscresolfluorene type epoxy resin, etc. The epoxy resin (a) may be used alone or in combination of two or more kinds. The epoxy equivalent of the epoxy resin (a) is preferably 150 to 350 g / eq. The purity of the epoxy resin (a) is preferably 95% by weight or more.
[0041] The bifunctional compound (B) used in the epoxy resin composition (E) may be any of the following: a diphenol compound (B1) having two hydroxyl groups bonded to an aromatic ring, a diester compound (B2) having two acyloxy groups bonded to an aromatic ring, or a monoester compound (B3) having one hydroxyl group and one acyloxy group bonded to an aromatic ring. The diester compound (B2) and the monoester compound (B3) may be referred to as "ester compounds" without distinction. Among these, the diphenol compound (B1) is preferred. The bifunctional compound (B) may suitably be one having a hydroxyl group equivalent or an ester group equivalent in the range of 80 g / eq. to 500 g / eq. The lower limit is preferably 100 g / eq., more preferably 110 g / eq. The upper limit is preferably 300 g / eq., more preferably 250 g / eq. The physical properties of the bifunctional compound (B), i.e., the specific values of the hydroxyl equivalent or ester equivalent, softening point or melting point, can be obtained from the catalog of the vendor of the commercially available material. The hydroxyl equivalent or ester equivalent can be calculated from the charge ratio or measured in accordance with the JIS K0070 standard. The softening point can also be measured by the ring and ball method described in JIS K7234-1986. The melting point can also be measured by the method described in JIS K0064-1992 or using a differential scanning calorimeter.
[0042] The purity of the bifunctional compound (B) is preferably 95% by weight or more. When monofunctional impurities are contained, the molecular weight after polymerization may not increase, and the mechanical properties of the produced thermoplastic resin may deteriorate. Therefore, the monofunctional impurities are preferably 2% by weight or less relative to the bifunctional compound (B). When trifunctional or higher impurities are contained, crosslinking structures are likely to be formed from the impurities, which may increase the dispersion of the polymerized product and may gel and impair the thermoplasticity. Therefore, the trifunctional or higher impurities are preferably 1% by weight or less relative to the bifunctional compound (B). If the purity of the bifunctional compound (B) is high, positional isomers may be contained. In addition, the bifunctional compound (B) may be used alone or in combination. The acyloxy group is represented by R-CO-O-, where R is a hydrocarbon group having 1 to 19 carbon atoms and may contain heteroatoms such as oxygen atom (O), sulfur atom (S), and nitrogen atom (N). The hydrocarbon group having 1 to 19 carbon atoms is preferably an alkyl group having 1 to 12 carbon atoms, an aryl group having 6 to 12 carbon atoms, an aralkyl group having 7 to 13 carbon atoms, or an unsaturated heterocyclic group having 4 to 19 carbon atoms.
[0043] The alkyl group having 1 to 12 carbon atoms may be linear, branched, or cyclic, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a t-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a t-pentyl group, a cyclopentyl group, an n-hexyl group, an isohexyl group, a cyclohexyl group, an n-heptyl group, a cycloheptyl group, a methylcyclohexyl group, an n-octyl group, a cyclooctyl group, an n-nonyl group, a 3,3,5-trimethylcyclohexyl group, an n-decyl group, a cyclodecyl group, an n-undecyl group, an n-dodecyl group, and a cyclododecyl group. Examples of the aryl group having 6 to 12 carbon atoms include a phenyl group, a tolyl group, an ethylphenyl group, a xylyl group, an n-propylphenyl group, an isopropylphenyl group, a mesityl group, a naphthyl group, and a methylnaphthyl group. Examples of the aralkyl group having 7 to 13 carbon atoms include a benzyl group, a methylbenzyl group, a dimethylbenzyl group, a trimethylbenzyl group, a phenethyl group, a 2-phenylisopropyl group, and a naphthylmethyl group. Examples of the unsaturated heterocyclic group having 4 to 19 carbon atoms include a furyl group having 4 carbon atoms, a thienyl group having 4 carbon atoms, a pyran skeleton substituent having 5 carbon atoms, a thiopyran skeleton substituent, a pyridyl group having 5 to 12 carbon atoms, an azanaphthyl group, and an azaanthracenyl group. Among these, an acyloxy group having a hydrocarbon group having 1 to 7 carbon atoms or an unsaturated heterocyclic group having 4 to 12 carbon atoms is preferable, an acetyloxy group, a propanoyloxy group, a butanoyloxy group, a benzoyloxy group, a methylbenzoyloxy group, a furyl group, a thienyl group, or a pyridyl group is more preferable, an acetyloxy group, a benzoyloxy group, a furyl group, or a thienyl group is even more preferable, and an acetyloxy group or a furyl group is particularly preferable.
[0044] Examples of the diphenol compound (B1) include bisphenol compounds such as bisphenol A, bisphenol F, bisphenol E, bisphenol Z, 2,4'-bisphenol S, bisphenol AP, bisphenol C, bisphenolacetophenone, bisphenoltrimethylcyclohexane, tetramethylbisphenol A, tetramethylbisphenol F, tetra-t-butylbisphenol A, dihydroxydiphenyl ether, dihydroxydiphenylmethane, thiodiphenol, and dihydroxystilbene; benzenediol compounds such as hydroquinone, methylhydroquinone, dibutylhydroquinone, resorcin, and methylresorcin; and phosphorus-containing phenol compounds such as dihydroxynaphthalene and diphenylphosphinylhydroquinone. In particular, when used in a reinforcing fiber-containing epoxy resin composition, a bisphenol compound is preferred. For the purpose of imparting flame retardancy, a phosphorus-containing phenol compound may be used.
[0045] The diester compound (B2) and the monoester compound (B3) include compounds in which two or one hydroxyl group of the diphenol compound (B1) is replaced with an acyloxy group (active ester). The diester compound (B2) is obtained by acylation of the diphenol compound (B1) with an acylating agent such as an acid anhydride of an organic acid, an organic acid halide, or an organic acid by condensation reaction. The monoester compound (B3) is also obtained by isolating from a mixture of the monoester compound (B3), the diester compound (B2), and the diphenol compound (B1) obtained by adjusting the molar ratio of the acylating agent during the acylation of the diphenol compound (B1). The melting point of the compound is lowered by performing acylation. Therefore, the compatibility with the epoxy resin is expected to improve.
[0046] Examples of the acid component used in the acylation include organic acids such as acetic acid, propionic acid, butyric acid, isobutyric acid, pentanoic acid, octanoic acid, caprylic acid, lauric acid, stearic acid, oleic acid, benzoic acid, t-butylbenzoic acid, hexahydrobenzoic acid, phenoxyacetic acid, acrylic acid, methacrylic acid, furancarboxylic acid, thiophenecarboxylic acid, and pyridinecarboxylic acid, as well as acid anhydrides of organic acids, halides of organic acids, and esters of organic acids. Examples of the acid anhydrides of organic acids include acetic anhydride, benzoic anhydride, phenoxyacetic anhydride, bis(2-furancarboxylic) anhydride, and bis(2-thiophenecarboxylic) anhydride. Examples of the esters of organic acids include methyl acetate, ethyl acetate, butyl acetate, methyl benzoate, ethyl benzoate, etc. Examples of the halides of organic acids include acetic acid chloride, benzoic acid chloride, phenoxyacetic acid chloride, 2-furancarboxylic acid chloride, 2-thiophenic acid chloride, etc. As these acylating agents, preferred are organic acid halides such as acetic acid chloride, benzoic acid chloride, phenoxyacetic acid chloride, 2-furancarboxylic acid chloride, and 2-thiopheneic acid chloride, and organic acid anhydrides such as acetic anhydride, benzoic acid anhydride, phenoxyacetic acid anhydride, and bis(2-furancarboxylic acid) anhydride. In order to avoid the need for washing with water after esterification and to avoid the inclusion of halogens, which are undesirable in electrical material applications, acid anhydrides such as acetic anhydride, benzoic acid anhydride, and bis(2-furancarboxylic acid) anhydride are more preferred, and acetic anhydride and bis(2-furancarboxylic acid) anhydride are even more preferred.
[0047] In the epoxy resin composition (E), the proportion of the bifunctional compound (B) is 0.90 to 1.10 mol, preferably 0.95 to 0.99 mol, and more preferably 0.97 to 0.98 mol, per 1.00 mol of the bifunctional epoxy resin (A). In the epoxy resin composition (E), the bifunctional epoxy resin (A) and the bifunctional compound (B) react successively to form a linear structure, which results in thermoplasticity. If the bifunctional epoxy resin (A) is in excess, the polymer will have an epoxy group terminal, and if the bifunctional compound (B) is in excess, the polymer will have a phenol group terminal or an acyloxy group terminal, and the reaction will terminate. If the ratio of the bifunctional compound (B) is more than 0.99 mol, the polymer will end up with a phenol group or acyloxy group end, and the reaction will terminate, which may make it difficult to increase the molecular weight. On the other hand, if the ratio of the bifunctional compound (B) is less than 0.95 mol, the excess epoxy groups may cause a side reaction, causing the polymer to gel and impairing thermoplasticity. Since the bifunctional epoxy resin (A) is bifunctional, its molecular weight corresponds to twice the epoxy equivalent. Similarly, the molecular weight of the bifunctional compound (B) corresponds to twice the functional group (hydroxyl group, acyl group) equivalent. Therefore, the molar ratio of the bifunctional compound (B) to the bifunctional epoxy resin (A) is the same as the equivalent ratio of the functional groups (hydroxyl group, acyl group) of the bifunctional compound (B) to the epoxy groups of the bifunctional epoxy resin (A).
[0048] An example of the diester compound (B2) is a compound represented by the following formula (3). [ka]
[0049] In formula (3), X and Y 1 , Y 2 , Y 3 is the same as that in equation (2).
[0050] The diester compound (B2) may be a phosphorus-containing compound, and examples of the phosphorus-containing compound include a cyclic phosphorus-containing compound represented by the following formula (4) (diacetylated product of DOPO-HQ). [ka]
[0051] When a phosphorus-containing epoxy resin or a phosphorus-containing bifunctional compound is used to impart flame retardancy to the epoxy resin composition (E), the phosphorus content is preferably 1% by weight to 6% by weight, more preferably 1.5% by weight to 5% by weight, and even more preferably 2% by weight to 4% by weight, based on 100% by weight of the total amount of the epoxy resin (A) and the compound (B). Moreover, instead of blending a phosphorus-containing compound as the bifunctional epoxy resin (A) or the bifunctional compound (B), or in addition to such a phosphorus-containing compound, various other known phosphorus-containing compounds may be blended into the epoxy resin composition (E).
[0052] In addition, impurity components that do not have active groups that react with either the bifunctional epoxy resin (A) or the bifunctional compound (B) and do not inhibit the polymerization reaction by themselves, such as non-reactive impurities derived from raw materials, may cause the molecular weight after polymerization to become small if their amount increases. Therefore, it is preferable that the amount of such impurity components is 2% by weight or less with respect to both the bifunctional epoxy resin (A) and the bifunctional compound (B).
[0053] In the epoxy resin composition (E), it is preferable that the epoxy resin (A) and the compound (B) are uniformly dissolved. If the compound (B) is present in the epoxy resin (A) in a crystalline state, the molar ratio deviates from the design when viewed microscopically. If the reaction is started in this state, the polymerization may not proceed sufficiently. In order to proceed sufficiently, an epoxy resin composition (E) in which the compound (B) and the epoxy resin (A) are mutually and uniformly compatible is preferable. In addition, it is preferable that the epoxy resin composition (E) before blending the reinforcing fibers and the like is completely compatible or in a uniform liquid state. For example, when the molten mixture is poured into a glass petri dish without air bubbles to a thickness of 2 mm and the haze value in the thickness direction is measured, if the haze value in the thickness direction is less than 30%, it can be judged that the mixture is dissolved to a level that does not affect the polymerization reaction or is in a uniform liquid state.
[0054] In order to obtain an epoxy resin composition (E) in which the compound (B), the epoxy resin (A), and the polymerization catalyst (D) are uniformly compatible with each other, it is preferable to make them compatible by heating. As a method of making them compatible by heating, there is a method of heating a mixture (M) of the epoxy resin (A) and the compound (B) containing the polymerization catalyst (D), or a method of heating a mixture (M) of the epoxy resin (A) and the compound (B) not containing the polymerization catalyst, obtaining an epoxy resin composition (C) in which they are uniformly compatible, and then adding the polymerization catalyst (D). If the mixture (M) of the epoxy resin (A) and the compound (B) containing the polymerization catalyst (D) is heated to a temperature at which the compound (B) is compatible, there is a risk of the polymerization reaction running out of control. In the method of heating the mixture (M) of the epoxy resin (A) and the compound (B) not containing the polymerization catalyst (D), the reaction does not proceed, but there is a risk that by-products that become multifunctional components that are the source of branching will be generated due to excessive heat history in a catalyst-free state, and the degree of branching of the polymerized product will increase. Therefore, in obtaining the epoxy resin composition (E), it is preferable to adopt a method in which a mixture of the compound (B) and the epoxy resin (A) is heated in advance with a minimum thermal history to obtain an epoxy resin composition (C) in which the compounds are uniformly dissolved, and then the polymerization catalyst (D) is added thereto.
[0055] Examples of the polymerization catalyst (D) that can be used in the present invention include N-substituted aminopyridine compounds, phosphine compounds, quaternary phosphonium salt compounds, imidazole compounds, and tertiary amine compounds. These polymerization catalysts (D) may be used alone or in combination of multiple types. Among these, N-substituted aminopyridine compounds and phosphine compounds are particularly preferred.
[0056] The N-substituted aminopyridine compound that can be used in the present invention is preferably an N-substituted aminopyridine compound represented by formula (5). [ka]
[0057] In formula (1), R 1 and R 2are independently a hydrocarbon group having 1 to 12 carbon atoms, and R 1 and R 2 may be bonded to each other to form a heterocycle, and the bond is -O-, -NH-, or -NR 4 - may be present. However, R 4 is a hydrocarbon group having 1 to 12 carbon atoms, preferably an alkyl group having 1 to 3 carbon atoms. Examples of the hydrocarbon group having 1 to 12 carbon atoms include an alkyl group having 1 to 12 carbon atoms, an aryl group having 6 to 12 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms. The alkyl group having 1 to 12 carbon atoms may be linear, branched, or cyclic, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a t-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a t-pentyl group, a cyclopentyl group, an n-hexyl group, an isohexyl group, a cyclohexyl group, an n-heptyl group, a cycloheptyl group, a methylcyclohexyl group, an n-octyl group, a cyclooctyl group, an n-nonyl group, a 3,3,5-trimethylcyclohexyl group, an n-decyl group, a cyclodecyl group, an n-undecyl group, an n-dodecyl group, and a cyclododecyl group. Examples of the aryl group having 6 to 12 carbon atoms include a phenyl group, an o-tolyl group, a m-tolyl group, a p-tolyl group, an ethylphenyl group, a styryl group, a xylyl group, an n-propylphenyl group, an isopropylphenyl group, a mesityl group, an ethynylphenyl group, a naphthyl group, and a vinylnaphthyl group. Examples of the aralkyl group having 7 to 12 carbon atoms include a benzyl group, a methylbenzyl group, a dimethylbenzyl group, a trimethylbenzyl group, a phenethyl group, a 2-phenylisopropyl group, and a naphthylmethyl group. R 1 and R 2 is preferably an alkyl group having 1 to 3 carbon atoms, or a group having a cyclopentane ring or cyclohexane ring formed by bonding with each other.
[0058] R 3are each independently a hydrocarbon group having 1 to 12 carbon atoms, preferably an alkyl group having 1 to 3 carbon atoms. Examples of the hydrocarbon group having 1 to 12 carbon atoms include R 1 and R 2 Examples of such cases are given below. k is the substituent R 3 It is an integer of 0 to 4, preferably 0 or 1, and more preferably 0.
[0059] The substitution position of the N-substituted amino group may be any of the 2-, 3-, and 4-positions of the pyridine, but the 4-position is preferred, and a compound represented by the following formula (5A) is more preferred. [ka] In the formula, R 1 and R 2 is R in Eq. (1). 1 and R 2 is synonymous with.
[0060] Examples of the N-substituted aminopyridine compounds include 2-dimethylaminopyridine, 2-pyrrolidinopyridine, 2-(dimethylamino)-6-methylpyridine, 2-methylethylaminopyridine, 2-methylbutylaminopyridine, 2-diethylaminopyridine, 2-methylpropylaminopyridine, 2-pyrrolidino-4-methylpyridine, 2-pyrrolidino-5-methylpyridine, 2-pyrrolidino-6-methylpyridine, 2-morpholinopyridine, 3-dimethylaminopyridine, N,N-diethyl-3-pyridinamine, 4-dimethylaminopyridine, 4-diethylaminopyridine, 4-dipropylaminopyridine, 4-dibutylaminopyridine, 4-dibenzylaminopyridine, 4-dihexylaminopyridine, 4-dihexylaminopyridine, 4-dioctylaminopyridine, 4-dinonylaminopyridine, 4-didecylaminopyridine, 4-undecylaminopyridine, Aminopyridine, 4-dodecylaminopyridine, 4-dibenzylaminopyridine, 4-diphenylaminopyridine, 4-pyrrolidinopyridine, 4-piperidinopyridine, 4-(4-methylpiperidino)pyridine, 4-morpholinopyridine, 4-methylethylaminopyridine, 4-methylpropylaminopyridine, 4-methylbenzylaminopyridine, 4-methylphenylaminopyridine, 2-methyl-4-(dimethylamino)pyridine, 2-ethyl-4-(dimethylamino)pyridine, 2-phenyl-4-(dimethylamino)pyridine, 3-methyl-4-(dimethylamino)pyridine, 3-ethyl-4-(dimethylamino)pyridine, 3-phenyl-4-(dimethylamino)pyridine, 3,5-dimethyl-4-(dimethylamino)pyridine, 2,5-di-t-butyl-4-(dimethylamino)pyridine, 1-(pyridin-4-yl)azocane, and the like. These N-substituted aminopyridine compounds may be used alone or in combination of two or more.
[0061] Of these N-substituted aminopyridine compounds, 4-dimethylaminopyridine, 4-diethylaminopyridine, 4-dipropylaminopyridine, 4-dibutylaminopyridine, 4-dibenzylaminopyridine, 4-dihexylaminopyridine, 4-dihexylaminopyridine, 4-dioctylaminopyridine, 4-dinonylaminopyridine, 4-didecylaminopyridine, 4-undecylaminopyridine, 4-dodecylaminopyridine, 4-dibenzylaminopyridine, 4-diphenylaminopyridine, 4-pyrrolidinopyridine, 4-piperidinopyridine, 4-(4-methylpiperidino)pyridine, 4-morpholinopyridine, 4-methylethylaminopyridine, 4-methylpropylaminopyridine, 4-methylbenzylaminopyridine, and 4-methylphenylaminopyridine are preferred. Among these, 4-(dimethylamino)pyridine (formula (5a) below), 4-pyrrolidinopyridine (formula (5b) below), 4-piperidinopyridine (formula (5c) below), 4-(4-methylpiperidino)pyridine (formula (5d) below), 4-morpholinopyridine (formula (5e) below), and 4-piperazinopyridine (formula (5f) below) are more preferred, with 4-(dimethylamino)pyridine, 4-pyrrolidinopyridine, and 4-piperazinopyridine being even more preferred. [ka]
[0062] Examples of the phosphine compounds include triphenylphosphine, tris(paratoluyl)phosphine, tris(orthotoluyl)phosphine, and tris(paramethoxyphenyl)phosphine. Examples of quaternary phosphonium salt compounds include tributyl(methyl)phosphonium dimethyl phosphate, tributyl(ethyl)phosphonium diethyl phosphate, methyltributylphosphonium dimethyl phosphate (e.g., Hishicolin PX-4MP (manufactured by Nippon Chemical Industry Co., Ltd.)), methyltrioctylphosphonium dimethyl phosphate, and tetrabutylphosphonium o,o-diethylphosphorodithioate (e.g., Hishicolin PX-4ET (manufactured by Nippon Chemical Industry Co., Ltd.)). Examples of imidazole compounds include 4-methylimidazole, Curazole 1B2MZ, Curazole 1B2PZ, and Curazole TBZ (all manufactured by Shikoku Chemical Industry Co., Ltd.). Examples of the tertiary amine compounds include triethylamine and tributylamine. Other examples of the polymerization catalyst include crown ether complexes such as 18-crown-6 (18-C-6) / AcOK complex and 18-C-6 / KF complex, and metal chlorides.
[0063] The amount of the polymerization catalyst (D) is 0.01 to 10 parts by weight relative to 100 parts by weight of the total amount of the components other than the component D constituting the epoxy resin composition (for example, the total amount of the epoxy resin (A) and the compound (B), or the total amount including the component (S) when a small amount of the solvent (S) is used). If it is less than 0.01 part by weight, the productivity may decrease because it takes time in the on-site polymerization, and there is a possibility that it may be deactivated for some reason before the target molecular weight is reached. On the other hand, if it exceeds 10 parts by weight, while the polymerization reaction proceeds quickly, there is a possibility that the storage stability is impaired and a problem occurs in the process compatibility, and since it is a component that participates in the reaction but is not incorporated into the skeleton, there is a possibility that the physical properties after polymerization are impaired, and since it is expensive, it is economically disadvantageous. It is preferably 0.05 to 5.0 parts by weight, more preferably 0.1 to 3.0 parts by weight, and even more preferably 0.1 to 1.0 parts by weight. It can be appropriately selected by comprehensively considering the balance between the pot life and the polymerization time.
[0064] In the epoxy resin composition (E) of the present invention, other catalysts may be used in combination with the N-substituted aminopyridine compound as the polymerization catalyst (D). The other catalysts are not particularly limited as long as they are catalysts used in the epoxy resin manufacturing method called the "two-stage method". Examples include alkali metal compounds, organic phosphorus compounds, tertiary amines, quaternary ammonium salts, cyclic amines, imidazole compounds, etc. These other catalysts may be used alone or in combination of two or more. When used in a reinforcing fiber-containing epoxy resin composition, it is preferable not to contain other catalysts.
[0065] Although the epoxy resin composition (E) preferably does not contain an organic solvent, it may contain an organic solvent as a solvent for the polymerization catalyst (D) or for viscosity adjustment, if necessary. The organic solvent is not particularly limited as long as it does not inhibit the reaction between the epoxy resin (A) and the compound (B), but from the viewpoint of ease of availability, a hydrocarbon-based, ketone-based, or ether-based solvent is preferable. Specifically, toluene, xylene, acetone, methyl ethyl ketone, isobutyl ketone, cyclopentanone, cyclohexanone, diethylene glycol dimethyl ether, etc. can be mentioned. However, if a large amount of organic solvent is present during the reaction, it inhibits the polymerization reaction, and if the organic solvent remains in the polymer, it may deteriorate the mechanical properties and heat resistance. For this reason, when an organic solvent is blended, the ratio is 0.01% by weight or more and 10% by weight or less of the epoxy resin composition (E), preferably 4% by weight or less, and more preferably 2% by weight or less. When an organic solvent is blended, the lower limit is not limited, but it is usually 0.01% by weight or more, and more preferably 0.5% by weight or more.
[0066] The epoxy resin composition (E) preferably has a low viscosity in order to maintain the impregnation property into the reinforcing fibers. The viscosity (Pa s) when heated to 85°C is 100 or less, preferably 50 or less, more preferably 20 or less, and further preferably 16 or less. The lower limit of the viscosity is 0.1 or more, preferably 1 or more. The time until the viscosity doubles from the initially measured viscosity (viscosity doubling time) is preferably 30 minutes or more, more preferably 60 minutes or more.
[0067] The progress of polymerization of the epoxy resin composition (E) can be judged by the change in the weight average molecular weight of the polymer (thermoplastic resin). If the weight average molecular weight is increasing, the polymerization reaction may not be complete. The polymerization conditions for obtaining a thermoplastic resin from the epoxy resin composition are preferably a temperature of 100 to 200°C, more preferably 150 to 180°C, and a time of preferably 30 minutes to 2 hours, more preferably within 1 hour.
[0068] The progress of polymerization of the reinforcing fiber-containing epoxy resin composition can also be judged from the transition of the weight average molecular weight of the polymer. The polymerization conditions for obtaining a fiber-reinforced thermoplastic resin polymer from the reinforcing fiber-containing epoxy resin composition are preferably a temperature of 100 to 200°C and a time of 2 to 5 hours.
[0069] The impact strength of the polymer is preferably 10 kJ / m 2 More preferably, 20 kJ / m 2 More preferably, 40 kJ / m 2 The upper limit is not particularly limited, but for manufacturing reasons, it is generally set to 100 kJ / m 2 That's about it.
[0070] When a phosphorus-containing compound is used as a raw material, the phosphorus content of the polymer is preferably 1 to 6% by weight, more preferably 1.5 to 5% by weight, and further preferably 2 to 4% by weight.
[0071] The epoxy resin composition (E) may contain additives. Examples of additives include fillers such as fumed silica, flame retardants such as aluminum hydroxide and red phosphorus, modifiers such as core-shell rubber, and viscosity adjusters such as xylene resin. From the viewpoint of stabilizing the polymerization reaction, it is preferable that additives different from the resin phase are blended, but plasticizers and compatible flame retardants may be included within the range that does not affect the reaction.
[0072] The epoxy resin composition (E) becomes a high molecular weight thermoplastic resin (phenoxy resin) by polymerization. This thermoplastic resin is excellent as a resin component for fiber reinforced plastics. The reinforcing fiber-containing epoxy resin composition of the present invention can be obtained by mixing or impregnating the above-mentioned epoxy resin composition (E) with the reinforcing fiber (F). The prepreg can be obtained as follows.
[0073] The epoxy resin composition (E) is applied to a release-treated paper or plastic film, and a release-treated cover film is applied as necessary to obtain an epoxy resin composition film. The release paper, release plastic film, and cover film can be any known one, and are not particularly limited. The thickness of the epoxy resin composition film is determined by the design thickness and resin ratio of the prepreg, and is usually 1 μm or more and 300 μm or less. If the thickness is less than 1 μm, there is a problem that the opening of the fiber becomes noticeable unless the reinforcing fiber is defibrated cleanly, and if the thickness exceeds 300 μm, it is difficult to uniformly impregnate the reinforcing fiber. The thickness is preferably 5 μm or more and 150 μm or less, and more preferably 10 μm or more and 100 μm or less.
[0074] The reinforcing fiber (F) used in the present invention is for reinforcing plastics such as carbon fiber, aramid fiber, cellulose fiber, and basalt fiber, and is not particularly limited. The form of the fiber is also not particularly limited, and includes UD sheets, woven fabrics, tows, chopped fibers, nonwoven fabrics, paper, etc., in which the fibers are aligned. However, from the viewpoint of impregnation, the thickness of each fiber bundle is 1 mm or less, preferably 0.5 mm or less, and more preferably 0.2 mm or less.
[0075] The reinforcing fiber-containing epoxy resin composition or prepreg of the present invention is obtained from the above-mentioned epoxy resin composition and / or epoxy resin composition film and reinforcing fiber. The ratio of reinforcing fiber to epoxy resin composition is preferably 2:8 to 8:2 by weight. In terms of resin content (Rc), it is 20 to 80% by weight, and it is possible to increase the ratio of reinforcing fiber, and if necessary, Rc can be made 35% by weight or less. If the ratio of reinforcing fiber is too small, the strength required for the fiber-reinforced material may not be fully satisfied, and if the ratio of reinforcing fiber is too large, defects such as voids may occur. The fiber reinforced plastic of the present invention preferably has an impact strength of 250 kJ / m 2 More preferably, 300 kJ / m 2 More preferably, 350 kJ / m 2 The upper limit is not particularly limited, but for manufacturing reasons, it is generally not more than 700 kJ / m 2 That's about it. EXAMPLES
[0076] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. Unless otherwise specified, "parts" refers to parts by weight, and "%" refers to % by weight. Furthermore, the unit of various equivalents is "g / eq." The raw materials, polymerization catalysts, solvents, and reinforcing fibers used in the examples are as follows.
[0077] [Epoxy resin] A1: Tetramethylbiphenol type epoxy resin (manufactured by Mitsubishi Chemical Corporation, YX4000, epoxy equivalent 186, melting point 105°C) [ka] A2: Tetramethylbisphenol F type epoxy resin (Nippon Steel Chemical & Material Co., Ltd., YSLV-80XY, epoxy equivalent 192, melting point 81℃) [ka] A3: Bisphenol A type epoxy resin (manufactured by Nippon Steel Chemical & Material Co., Ltd., YD-8125, epoxy equivalent 172, melting point 42°C) [ka]
[0078] [Phenol compounds, ester compounds] B1: Bisphenol A (manufactured by Nippon Steel Chemical & Material Co., Ltd., hydroxyl equivalent 114, melting point 158°C) [ka] B2: 4,4'-bis(3,3,5-trimethylcyclohexylidene)bisphenol (Honshu Chemical Industry Co., Ltd., BisP-HTG, hydroxyl equivalent 155, melting point 206°C) [ka] B3: 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (manufactured by Sanko Co., Ltd., HCA-HQ, hydroxyl equivalent 162, melting point 250° C.), used as a raw material in Synthesis Example 1. [ka] B4: Bifunctional acetylated compound obtained in Synthesis Example 1 (10-(2,5-diacetoxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, phosphorus content 7.6%, acetyl group equivalent 204, melting point 140° C.) [ka]
[0079] [Polymerization catalyst] D1: 4-Dimethylaminopyridine (Tokyo Chemical Industry Co., Ltd., DMAP) [ka] D2: Tris(p-methoxyphenyl)phosphine (TPAP, manufactured by Hokko Chemical Industry Co., Ltd.) [ka] D3: Methyltributylphosphonium dimethylphosphate (Nippon Chemical Industry Co., Ltd., Hishicolin PX-4MP) [ka] D4: 2,3-dihydro-1H-pyrrolo-[1,2-a]benzimidazole (Curesol TBZ, manufactured by Shikoku Chemical Industry Co., Ltd.) [ka] D5: Tri-o-tolylphosphine (TOTP, manufactured by Hokko Chemical Industry Co., Ltd.) [ka]
[0080] [others] S: Cyclohexanone F: PAN-based carbon fiber (Toray Industries, Torayca T700-12K-60E)
[0081] The evaluation methods used in the examples are as follows. (1) Epoxy equivalent: The measurements were performed in accordance with JIS K7236 and expressed in units of g / eq. Specifically, a potentiometric titrator (HIRANUMA SANGYO CO., LTD., COM-1600ST) was used, chloroform was used as the solvent, a tetraethylammonium bromide acetate solution was added, and a 0.1 mol / L perchloric acid-acetic acid solution was used.
[0082] (2) Glass transition temperature (Tg): The measurement was performed in accordance with the JIS K7121 standard. Specifically, using a differential scanning calorimeter EXSTAR6000 DSC6200 (manufactured by Hitachi High-Tech Science Corporation), two cycles were measured in the range of 20 to 200°C at a temperature increase rate of 10°C / min, and the midpoint glass transition temperature (Tmg; the midpoint temperature of the transition curve with respect to the tangent line between the glass state and the rubber state) of the measurement chart obtained by the second scan was expressed.
[0083] (3) Weight average molecular weight (Mw) and slope α of the MH plot (degree of branching) measured by the absolute molecular weight measurement method (viscosity method) The measurement was performed by light scattering GPC. Specifically, a main body OMNISEC (manufactured by Malvern) equipped with columns TSKgel guardcolumn MP (XL), TSKgel Multipore HXL-M, and TSKgel G1000HXL (all manufactured by Tosoh Corporation) in series was used, and the column temperature was set to 40°C. The eluent used was tetrahydrofuran (THF), with a flow rate of 1.0 mL / min, and the detectors used were a differential refractive index detector (RI detector), a light scattering detector (RALS 90°, LALS 7°), and a viscosity detector. The measurement sample was prepared by dissolving 0.02 g of the cured product in 10 mL of THF and filtering through a 0.20 μm microfilter, and the injection amount was 100 μL. The data was processed using OMNISEC-11.10 (manufactured by Malvern). The weight-average molecular weight (Mw) was calculated using the following procedure: First, the molecular abundance ratio (area per minute section / area of the entire peak) was calculated using an RI detector, then the absolute molecular weight (M) for each minute section was detected using a light scattering detector, and the weight-average molecular weight (Mw) was calculated from the relationship between the obtained minute section and the absolute molecular weight (M). The intrinsic viscosity (η) for each small interval was analyzed using a viscosity detector, and a Mark-Houwink-Sakurada plot (MH plot) was created from the absolute molecular weight (M) and intrinsic viscosity (η) values, and the slope α (degree of branching) was calculated for absolute molecular weights (M) in the range of 50,000 to 100,000. Here, the closer the slope α value is to 0, the more the structure resembles a sphere with many branches, and the closer it is to 1, the more linear the structure with fewer branches.
[0084] (4)Impact strength: Measurements were performed according to the JIS K7111-1 standard for notched Charpy impact tests (edgewise impact). The test machine used was a digital impact tester DG-UB type (manufactured by Toyo Seiki Seisakusho Co., Ltd.), with a lift angle of 150°. The hammer used was selected from those with nominal pendulum energies of 0.5J, 1J, 2J, 4J, 7.5J, and 15J. The dimensions of the sample were 4mm thick, 80mm long, and 10mm wide, and the notch was machined to create an A-notch (notch width: 8.0mm, radius: 0.25mm). The hammer was dropped onto the sample, and the impact strength was calculated from the hammer's swing-up angle after measurement.
[0085] Synthesis Example 1 (Ester Compound) In a glass reaction vessel equipped with a stirrer, a thermometer, a nitrogen gas introduction device, a cooling tube, and a dropping device, 162 parts of a bifunctional phenol compound (B3), 105 parts of acetic anhydride, and 79 parts of pyridine were charged at room temperature, and the mixture was heated to 60°C while stirring under nitrogen gas flow, and reacted for 2 hours. After that, the mixture was dried under reduced pressure at 150°C and 1.3 kPa (10 torr) for 2 hours, to obtain 203 parts of a phosphorus-containing compound (B4) represented by the above formula (4).
[0086] Example 1 144 parts of tetramethylbiphenol type epoxy resin (A1), 50 parts of bisphenol A (B1), and 50 parts of 4,4'-bis(3,3,5-trimethylcyclohexylidene)bisphenol (B2) were each weighed out and pulverized and mixed using a Henschel mixer to obtain a mixture (M1). 100 parts of the mixture (M1) was weighed out and melt-mixed using a single screw extruder (IKG Corporation, RMS30-28, L / D=28, full flight screw, cylinder temperature 200°C) with the barrel temperature set to 170°C. The rotation speed was set to 40 rpm so that the residence time in the extruder was 1 minute. The entire amount of the molten resin was collected in a metal can and quickly cooled to 85°C to obtain an epoxy resin composition. 0.1 parts of 4-dimethylaminopyridine (D1) was added as a polymerization catalyst to 100 parts of the obtained epoxy resin composition, and mixed in a state heated to 85°C. After mixing, the mixture was quickly removed and immediately cooled to 20°C to obtain an epoxy resin composition (E1).
[0087] The obtained epoxy resin composition (E1) was heated to about 85°C and stirred, poured into a chrome-plated iron mold container with a clearance of 4 mm in advance, and thermally polymerized in a hot air circulating oven at 160°C for 60 minutes to obtain a polymer (resin plate). The weight-average molecular weight of the obtained polymer was measured to find that Mw was 79,000, the slope α of the MH plot in the absolute molecular weight (M) range of 50,000 to 100,000 was 0.53, the epoxy equivalent was 33,000, Tg was 135°C, and the notched Charpy impact strength was 42 kJ / m 2 It was.
[0088] A release-treated release paper was fixed on a hot plate preheated to 85°C with the release side facing up, and the epoxy resin composition (E1) was placed on the release paper. Then, a bar coater preheated to 85°C was used to coat the epoxy resin composition until the area weight of the resin was 79 g / m. 2 Immediately after coating, the sheet was removed from the hot plate and cooled in air to obtain an epoxy resin composition sheet. Next, a fiber sheet having an area weight of 153 g / m was applied onto the obtained epoxy resin composition sheet. 2 A hot press preheated to 90°C was used to apply pressure to a surface pressure of 0.5 MPa, and the prepreg was removed after 1 minute and air-cooled to obtain a prepreg with Rc = 34%. 28 sheets of the obtained prepregs were laminated with the fibers oriented in the same direction, and then release films were attached to the top and bottom surfaces, and the prepreg was sandwiched between 3 mm thick aluminum plates. The aluminum plates sandwiching the prepregs and the coupler were then wrapped in bag film, and the coupler was connected to a vacuum pump, and the air inside the bag film was evacuated. The bag was placed in a hot air circulating oven that had been preheated to 160°C, and curing was carried out while maintaining the vacuum, forming a 4 mm thick unidirectional fiber reinforced plastic (CFRP plate). The curing conditions were 160°C and 240 minutes. The notched Charpy impact strength of the obtained unidirectional fiber reinforced plastic was measured and found to be 370 kJ / m 2 It was.
[0089] Examples 2 to 5, Comparative Examples 1 to 3 The ingredients were mixed in the amounts (parts) shown in Table 1, and the same operations as in Example 1 were carried out to obtain epoxy resin compositions (E2 to E8), polymers, epoxy resin composition sheets, prepregs, and unidirectional reinforced fiber plastics. E6 to E8 are comparative examples. In Example 4 and Comparative Examples 2 to 3, when the polymerization catalysts (D2, D4, D5) were added, the polymerization catalysts were dissolved in cyclohexanone (S) beforehand and then added in a predetermined amount. In Example 2, the polymerization conditions for the resin plate were 180°C and 60 minutes, and the polymerization conditions for the CFRP were 180°C and 240 minutes. The obtained polymer and unidirectional reinforced fiber plastic were measured for each physical property in the same manner as in Example 1, and the evaluation results are shown in Table 1. In addition, the "molar ratio" in the table indicates the molar ratio (equivalent ratio) of the hydroxyl group of the phenol compound and the acyl group of the ester compound to the epoxy group of the epoxy resin.
[0090] [Table 1] [Industrial Applicability]
[0091] The epoxy resin composition of the present invention is useful as a matrix resin for fiber-reinforced plastics (FRP), and is particularly suitable for use as an in-situ polymerized thermoplastic epoxy resin.
Claims
1. An epoxy resin composition comprising, as essential components, an epoxy resin (A) having two epoxy groups in one molecule, a compound (B) having two functional groups reactive with epoxy groups in one molecule, and a polymerization catalyst (D), which becomes a thermoplastic resin by a polymerization reaction, The blending amounts of the epoxy resin (A) and the compound (B) are 0.90 to 1.10 moles of the compound (B) per mole of the epoxy resin (A), A thermoplastic resin obtained by polymerizing an epoxy resin composition is characterized in that the slope α of a Mark-Houwink-Sakurada plot (M-H plot) in the absolute molecular weight range of 50,000 to 100,000 measured by light scattering GPC is 0.45 or more and 0.80 or less.
2. 2. The epoxy resin composition according to claim 1, wherein the content of the polymerization catalyst (D) is 0.01 parts by weight or more and 10 parts by weight or less per 100 parts by weight of the total amount of the epoxy resin (A) and the compound (B).
3. 2. The epoxy resin composition according to claim 1, characterized in that it does not contain an organic solvent, or if it contains an organic solvent, the content of the organic solvent is 0.01% by weight or more and 10% by weight or less of the epoxy resin composition, and the epoxy resin (A) and the compound (B) are uniformly dissolved in the epoxy resin composition.
4. A reinforcing fiber-containing epoxy resin composition comprising the epoxy resin composition according to any one of claims 1 to 3 and reinforcing fibers (F).
5. 5. The reinforcing fiber-containing epoxy resin composition according to claim 4, wherein the reinforcing fiber (F) is a continuous fiber.
6. 5. The reinforcing fiber-containing epoxy resin composition according to claim 4, characterized in that the reinforcing fiber (F) is carbon fiber in an amount of 20 to 80% by weight.
7. A prepreg comprising the reinforcing fiber-containing epoxy resin composition according to claim 4.
8. A fiber-reinforced plastic using the reinforcing fiber-containing epoxy resin composition according to claim 4.
9. A fiber reinforced plastic using the prepreg according to claim 7.
10. A thermoplastic resin obtained from the epoxy resin composition according to any one of claims 1 to 3, characterized in that the slope α of a Mark-Houwink-Sakurada plot (M-H plot) measured by light scattering GPC at an absolute molecular weight of 50,000 to 100,000 is 0.45 or more and 0.80 or less.
11. A prepreg comprising the thermoplastic resin according to claim 10 and reinforcing fibers (F).
12. A fiber-reinforced plastic comprising the thermoplastic resin according to claim 10 and reinforcing fibers (F).
13. A fiber reinforced plastic using the prepreg according to claim 11.
Citation Information
Patent Citations
Method for molding fiber-reinforced thermoplastic resin
JP2006321897A
Bisphenol f skeleton-containing phenoxy resin, manufacturing method therefor and resin composition using the same
JP2017171802A
Method for producing fiber-reinforced thermoplastic plastic and fiber-reinforced thermoplastic prastic
WO2004060981A1